2021
DOI: 10.3390/catal11030403
|View full text |Cite
|
Sign up to set email alerts
|

Modified-TiO2 Photocatalyst Supported on β-SiC Foams for the Elimination of Gaseous Diethyl Sulfide as an Analog for Chemical Warfare Agent: Towards the Development of a Photoreactor Prototype

Abstract: In the context of the increase in chemical threat due to warfare agents, the development of efficient methods for destruction of Chemical Warfare Agents (CWAs) are of first importance both for civilian and military purposes. Amongst possible methods for destruction of CWAs, photocatalytic oxidation is an alternative one. The present paper reports on the preparation of Ta and Sn doped TiO2 photocatalysts immobilized on β-SiC foams for the elimination of diethyl sulfide (DES) used as a model molecule mimicking Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Although photocatalyzed sulfide oxidation has already been reported in the literature, the system developed in this work compares favorably to already known procedures, especially those operating in the gas phase 22 (which is the most relevant model of sulfur mustard exposure). In fact, other systems require either specific light irradiation sources, 23 complex catalysts, 24 pure oxygen atmosphere, 25 high catalytic loadings, 26 or fall short in terms of selectivity, 27 stability and/or recyclability. 28 Taken together, these limitations highlight the effectiveness of the supported TPPcatalyst which is active under air in the absence of solvent, requires as little as 0.1 mol% loading, and can be readily recycled and reused with no alteration of catalytic performances.…”
Section: Catalysis Science and Technology Communicationmentioning
confidence: 99%
“…Although photocatalyzed sulfide oxidation has already been reported in the literature, the system developed in this work compares favorably to already known procedures, especially those operating in the gas phase 22 (which is the most relevant model of sulfur mustard exposure). In fact, other systems require either specific light irradiation sources, 23 complex catalysts, 24 pure oxygen atmosphere, 25 high catalytic loadings, 26 or fall short in terms of selectivity, 27 stability and/or recyclability. 28 Taken together, these limitations highlight the effectiveness of the supported TPPcatalyst which is active under air in the absence of solvent, requires as little as 0.1 mol% loading, and can be readily recycled and reused with no alteration of catalytic performances.…”
Section: Catalysis Science and Technology Communicationmentioning
confidence: 99%
“…Various photoreactors under artificial light sources were proposed in previous studies, such as the slurry reactors [8,9], fluidized-bed reactors [10][11][12], fixed-bed reactors [13][14][15], optical fiber illuminating reactors [16] and optical fiber monolith reactors (OFMR) [17,18], among which the OFMR structure firstly reported by Lin and Valsaraj et al [19] stands out because the inserted fiber illuminating structure increases quantum efficiency [20]. What is more, the catalyst coated on the surface of optical fibers and monoliths increases the reaction capacity, and the direct reaction channels lower the pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…To make breakthroughs for superior force protection against CWAs, many self-cleaning materials such as metal–organic frameworks and metal (hydr)­oxide, have been synthesized to decompose these deadly chemicals through oxidation or hydrolysis. ,, Specifically, photocatalytic oxidation has become a promising route due to its advantages of energy conservation and environmental friendliness . Recent researches indicated that TiO 2 and its composites displayed intriguing photocatalytic activities toward CWAs and their mimetics. Significantly, TiO 2 -based composites could achieve notably higher photocatalytic efficiencies than the TiO 2 through the addition of extra additives. , Unfortunately, the majority of these composites exist in the powder form, which leads to serious agglomeration and makes them less effective in terms of offering enough active sites for catalysis. Hence, the huge challenge is to construct stereoscopic bulks from TiO 2 that give an additional dimension of functionality as well as to perfectly conquer the intrinsic brittleness and the low photocatalytic activity.…”
mentioning
confidence: 99%